Human Capital Management Development and Environment Policy Model on The Performance of State Civil Apparatus in Riau Province Government - Syarifuddin , Said; Indarti, Sri; ., Machasin; ., Samsir (Journal of Ecohumanism, 2024)
This study aims to develop a conceptual framework for Competence-based Human Capital Management (HCM) and Religiosity to the Performance of the State Civil Apparatus (ASN) in the Riau Provincial Government. This study is to find the most appropriate way to develop ASN competence and fill in the limitations of previous research and gaps in competency research on ASN performance. This study uses a quantitative approach by distributing questionnaires to officials related to the development of ASN competencies, both Structural Officials ranging from Middle High Officials, Primary High Officials, Administrator, and Supervisory Officers, as well as Functional Officers related to competency development, as many as 114 respondents with using a purposive sampling approach, data collection techniques using a questionnaire with a scale of 1-5, which then uses Structural Equation Modeling-Partial Least Square (PLS) analysis with the outer Model, and inner model and processed using the SmartPLS 3. Capital Management and Supported by Religiosity. This study examines the development of competence based on Human Capital Management and Religiosity as a moderator of ASN performance. This research has never been conducted simultaneously.